ANALISIS TERHADAP IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Ulfa Mariatul Kiptiyah; Umi Karimatul Azizah (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2026)
The implementation of the Independent Curriculum in Islamic educational institutions requires regulatory readiness and thorough institutional adaptation to prevent a decline in students' moral qualities. This study aims to in-depth evaluate the implementation of the independent learning concept in Islamic Religious Education (PAI) at the Madrasah Tsanawiyah (Islamic Junior High School) level. Using a descriptive qualitative approach, this study employed a literature review method using relevant literature sources published between 2020 and 2026, supported by comprehensive document analysis techniques. The review revealed that the implementation of this new curriculum faces crucial obstacles, particularly the low preparedness of teachers in developing competency assessment instruments and operationalizing the essence of learning differentiation. Furthermore, the integration of religious subject matter clusters, including Aqidah (Akhlak), Fiqh (Islamic Jurisprudence), and Islamic Cultural History, has not been optimally organized within a project-based teaching scheme. Based on these findings, the main conclusion confirms that the successful implementation of this program relies heavily on educators' methodological skills in designing autonomous learning. Optimizing the Pancasila Student Profile Strengthening Project (P5) is considered to have significant potential to mitigate students' non-technical skills lag. This synergy is designed to create an interactive instructional process to produce a young generation that is knowledgeable, faithful, and has noble morals. ABSTRAK Penerapan Kurikulum Merdeka di lembaga pendidikan Islam menuntut kesiapan regulasi serta adaptasi institusional yang matang agar tidak memicu penurunan kualitas moral siswa. Penelitian ini bertujuan untuk mengevaluasi secara mendalam pelaksanaan konsep pembelajaran mandiri pada mata pelajaran Pendidikan Agama Islam (PAI) di tingkat Madrasah Tsanawiyah. Melalui pendekatan kualitatif deskriptif, studi ini menerapkan metode literatur menggunakan sumber pustaka relevan terbitan tahun 2020-2026 yang diperkuat dengan teknik analisis dokumen secara komprehensif. Hasil telaah menunjukkan bahwa eksekusi kurikulum baru ini menghadapi kendala krusial, terutama rendahnya kesiapan guru dalam menyusun instrumen penilaian capaian kompetensi serta mengoperasikan esensi diferensiasi belajar. Selain itu, integrasi rumpun materi keagamaan yang meliputi Akidah Akhlak, Fikih, dan Sejarah Kebudayaan Islam belum terorganisasi secara maksimal dalam skema pengajaran berbasis proyek. Berdasarkan temuan tersebut, kesimpulan utama menegaskan bahwa keberhasilan implementasi program ini sangat bertumpu pada kecakapan metodologis pendidik dalam merancang pembelajaran otonom. Optimalisasi Proyek Penguatan Profil Pelajar Pancasila (P5) dinilai berpotensi besar memitigasi ketertinggalan kecakapan nonteknis siswa. Sinergi ini dirancang untuk mewujudkan proses instruksional interaktif demi mencetak generasi muda yang berilmu luas, beriman, sekaligus berakhlak mulia.